Concept of university competitiveness: tetrahedron model - A. . Grudzinskiy; A. . Bedny (Moscow Polytechnic University, 2022)
The new interpretation of a university functional model in the form of "tetrahedron" is suggested. Innovator being the main university's "product" is situated at the top of the tetrahedron. The tetrahedron demonstrates the unique competitive advantage of a university, as well as the unique position of the whole higher education system among other competitors on the global market of knowledge. It is shown that innovations are much more successfullyproduced by high-tech corporations, and universities should be primarily focused on raisinginnovators. Consequently, the competition among universities takes a form of struggle for quality of innovators' training.